Effect of Spray Drying Conditions on the Pyhsical Properties of Sugarcane (Saccharum officinarum) Powder - Mohamad Fuzi, Siti Fatimah Zaharah; Nurul Syazwani Ramli (Enhanced Knowledge in Sciences and Technology, 2022)
The objective of this study was to determine the effect of spray drying conditions on the physical qualities of sugarcane powder. The influence of maltodextrin concentrations (6 and 12 percent (w/v)) and inlet air temperatures (150, 160, and 170 °C) on the physical properties of spray-dried sugarcane powder were examined. A constant feed flow rate of 3Lh-1 was used, as well as a regulated air pressure rate. The mini spray dryer (SOLTEQ, model FD-20) was used in this study’s investigation. A significant decrease in the moisture content, water activity, bulk density, and solubility of the spray-dried products was observed for all inlet air temperatures applied. Inlet air temperatures of 150 °C, 160 °C, and 170 °C caused a significant decrease in the moisture content, water activity, bulk density, and solubility of the spray-dried products. The increased temperature of the incoming air improved the flowability or wettability of the products, hence increasing the operation’s product yield. Additionally, raising the maltodextrin concentration improved the bulk density (0.57-0.80 g/ml) and flowability (41.94 -52.10) of the spray dried products, while decreasing the solubility time (165.33 - 273.33 sec) and wettability time (5.23 - 115.33 sec). However, for all maltodextrin concentrations, there were no significant changes in the sugarcane powder’s moisture content (0.72 percent - 4.18 percent) or water activity (0.20 - 0.33). This study demonstrates that an inlet air temperature of 150 °C and a maltodextrin content of 12% (w/v) are the optimal conditions for producing sugarcane powder due to its favorable look and solubility. Additionally, this research discovery can be applied to the production of instant sugarcane beverages and other related commodities.